Identity after Impairment: Development of an Athletic Identity Model of Filipino Para-athletes - Lagundino, Marian M.; Reyes, Marc Eric S.; Cayubit, Ryan Francis O. (UI Scholars Hub, 2024)
Athletic Identity (AthID) is an aspect of the self-concept that refers to how one identifies with the role of an athlete and seeks acknowledgment of that role. This identity is not salient in all individuals, but AthID is activated for those who regard their athletic role as significant. Our objective was to develop a theoretical model to elucidate how Filipino para-athletes can cultivate their distinct athletic identity after acquiring a disability. The present study explored the athletic identities of 12 Filipino para-athletes, aged 24 to 63, who developed physical impairment and continued participating and competing in their chosen sports. Using the grounded theory method, we conducted in-depth interviews with our participants. Our findings showed that the transformation of athletes into para-athletes is a continuous journey shaped by internal reflections, external interactions, and personal development. This process ultimately leads to creating a distinct identity for para-athletes. It involves dealing with the challenges brought about by a disability, overcoming emotional and psychological obstacles, and ultimately embracing a para-athlete identity marked by inspiration, strength, and self-empowerment. Our athletic identity model of Filipino para-athletes suggests that transitioning from being an athlete to becoming a para-athlete is complex and diverse. This theory offers valuable knowledge about how people adjust and transform their sense of self after experiencing life-changing events.